The Influence Of Learning Motivation And Independence On Learning Outcomes Of Creative Project And Entrepreneurship (PKK) Subjects In SMK N 6 Padang - Annisa, Desfiarini; Yulastri, Asmar; Gusnita, Wiwik; Andriani, Cici (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research aims to describe and analyze the influence of motivation and learning independence on learning outcomes in the Creative Entrepreneurship Project (PKK) subject in the culinary department of SMK N 6 Padang. In this research, measurements will be carried out to determine the influence of motivation and learning independence on learning outcomes in the Creative Entrepreneurship Project (PKK) subject. This research uses a type of correlation research using a quantitative approach. In this study, the population and sample were the same, namely class XI students majoring in culinary, totaling 101 people. The sampling technique used is saturated sampling. Data collection was carried out via Google form and used a Likert scale whose validity and reliability had been tested. The data analysis techniques used are descriptive analysis tests, normality tests, linearity tests, multicollinearity tests, multivariate tests and correlation significance tests. The results of the research show that: 1) the correlation coefficient of motivation and learning independence on learning outcomes in PKK subjects is 0.256 which is included in the low category, 2) there is a significant influence between motivation and learning outcomes in PKK subjects with a sig value of 0.00 < 0, 05 so it can be concluded that H1 is accepted, 3) there is an influence between independence and learning outcomes in PKK subjects with a sig value of 0.002 < 0.05 so it can be concluded that H2 is accepted, 4) there is a simultaneous influence between motivation and independence on learning outcomes in PKK subjects with sig 0.000 < 0.05 and Fcount 8.659 > Ftable 3.09 .